2013
DOI: 10.12968/ijtr.2013.20.4.200
|View full text |Cite
|
Sign up to set email alerts
|

Developing the SELF study: A focus group with patients and the public

Abstract: Research and learning methodologies Developing the SELF study: A focus group with patients and the public Background: Patient and public involvement (PPI) in the research process is a key feature of NHS Research and Development policy but reporting of the extent and value of PPI in relation to physiotherapy research is lacking. Aims: To determine whether the proposed methodology within the randomized controlled trial aspect of the SELF study was acceptable to patients and to ascertain whether enhancements coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…5 Patients have initially expressed interest but not turned up; dropped out, despite promises of remuneration 5 , or felt less inclined to participate due to multiple trips to clinical environments. 26 However, this study experienced fewer barriers recruiting patients than suggested by much that is reported in the current literature. We suggest this may be attributed to our recruitment strategy on consultation with a PAG and taking their feedback into account, for example, a patient's clinical management of specialty, since people attend hospital many times in renal medicine and thus do not want to attend on a separate occasion.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…5 Patients have initially expressed interest but not turned up; dropped out, despite promises of remuneration 5 , or felt less inclined to participate due to multiple trips to clinical environments. 26 However, this study experienced fewer barriers recruiting patients than suggested by much that is reported in the current literature. We suggest this may be attributed to our recruitment strategy on consultation with a PAG and taking their feedback into account, for example, a patient's clinical management of specialty, since people attend hospital many times in renal medicine and thus do not want to attend on a separate occasion.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 85%
“…7 This approach of involving patients at every stage of the research process has previously been reported as lacking in earlier PPI initiatives. 6 Recruitment to PPI studies has been challenging for researchers, such as in physiotherapy PPI 26 and dementia PPI 27 who also reported difficulties recruiting. 7 This has similarly reflected recruitment strategies with larger clinical studies.…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 99%
“… High: in the exergame group ( n = 7) 7 weeks were correct, 5 weeks varied by <3/27 exercises across all participants. Case 4: SELF pilot Pilot pragmatic open trial comparing self-managed loaded PT exercise with usual PT for rotator cuff tendinopathy (single centre, private clinic) Experimental ( n = 12): Completion of sets of exercises per day (1 tick per session for 2 sessions a day) (3 months) ▪Interview ▪Sample diary ▪Viewed sample of completed diaries ▪Pilot results publication [ 43 ] ▪In -press results of substantive study ▪Substantive study protocol [ 44 ] ▪Qualitative pilot publication [ 45 ] ▪Patient and public involvement publication [ 46 ] 1 A4 page (×1–5); 7 items per week; frequency (tick); returned at each appointment High: 92 % (11/12) Medium-high: 7 complete data (all consecutive diaries), 4 partial data. Returned diaries were well-completed on viewing, with the occasional incorrect completion.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, research funding bodies and ethics committees are often mandated to consider the views of service users and the general public in their deliberations about study questions regardless of methodological orientation. In this capacity, qualitative methods offer the researcher the tools to understand patient and public concerns before study design, in development of research strategy and later, in dissemination of findings .…”
Section: The Qualitative–quantitative Debatementioning
confidence: 99%